Da'wah Communication in Maintaining Harmony Among Religious Communities - Nursafa’ah, Ati’; Fikri, Muhammad Rozan; Syafiri, Mohammad Afid; Huri, Vivi Silvia (Journal of Community Service and Empowerment, 2026)
This article discusses the role of da'wah communication in maintaining interfaith harmony, focusing on persuasive and empathetic da'wah strategies in interfaith communities. In the context of a multicultural society, da'wah is not only understood as the activity of conveying religious teachings, but also as a medium for social dialogue oriented towards strengthening the values of tolerance and social cohesion. This study uses a qualitative method with a descriptive analytical approach to explore forms of da'wah communication that can bridge differences in beliefs and build harmonious relations between people. Data were obtained through in-depth interviews, participatory observation, and documentation of interfaith da'wah activities organized by religious leaders and religious institutions at the community level. The results show that persuasive da'wah strategies that emphasize dialogue, respect for differences, and the delivery of moral messages in a humanistic manner are capable of fostering social empathy and strengthening a sense of togetherness amid plurality. The empathetic approach taken by preachers has proven effective in reducing interfaith prejudice and enhancing constructive social interaction. Thus, da'wah communication based on persuasive and empathetic values plays a significant role in maintaining harmony and strengthening social cohesion in a pluralistic society.